Construção e reconstrução de valores relativos à competição organizacional: acompanhando a mudança contínua de uma prestadora de serviços - Tussi, Alessandra Colla Soletti (2016)
Organizational change may be viewed from an ongoing standpoint as a process emerging from the daily actions of players functioning within the organizational sphere over time, through experiences and adjustments to everyday contingencies (ORLIKOWSKI, 1996), in a constant corporate coming-to-be construction process (TSOUKAS; CHIA, 2002). Underlying these daily actions by players pursuing resources in a competitive context are values related to organizational competition – VROC (DOMENICO, 2007a). Steered by this understanding, and taking into consideration the importance of longitudinal studies for understanding corporate changes (MINTZBERG, 1979; PETTIGREW, 1990; VAN DE VEN; HUBER, 1990; VAN DE VEN; POOLE, 1995; BEER; EISENSTAT, 1996; ORLIKOWSKI, 1996), we extend a project undertaken by Brazil’s National Council for Scientific and Technological Development (CNPq), under the aegis of the Values, Dignity and Management research group. Moving ahead with studies that began with the CMA company, selected for its unusual management approach, we identify and analyze which VROCs were maintained, abandoned or re-signified during the coming-to-be process of this company from 2013 through to yearend 2015. Using a qualitative method grounded on the single case study research strategy with a cross-sectional approach, 22 semi-structured interviews constituted the sources of evidence, together with non-participant observations, spontaneous conversations and documents. Through analyzing these data, it was noted that the following VROCs were maintained: ‘coherence between what is said and what is done’; ‘informality’; ‘commitment to results’; ‘specialized knowledge’; ‘innovation’; and ‘freedom’, while ‘collective participation’ and ‘primacy of the human being’ VROCs were re-signified. Moreover, ‘commitment to the founder’ was discontinued, replaced by the new organizational competition value of ‘commitment to the managing partners’ which was built up during the period covered by this study, together with the ‘personal effort’ and ‘collaboration’ VROCs. We also noted that the organization continues to stand out from mainstream management styles in its sector through upholding certain aspects rated as comparative advantages over other firms in the fiscal and tax segment. As academic contributions, we contribute to the understanding of ongoing change as a coming-to-be process through analyzing values related to organizational competition, viewed as institutionalized and relatively provisional categories. As practical contributions, we offer administrators a reflection on understanding organizational changes beyond the episodic approach, showing how companies can stand out through mainstream management practices.